Flexible morphology-controlled synthesis of monodisperse α-Fe2O3 hierarchical hollow microspheres and their gas-sensing properties - Song, Hao-Jie (2017)
Microspheres constructed with α-FeOOH nanorods were fabricated by a sodium dodecylbenzenesulfonate (SDBS) assisted hydrolysis process in an ethanol/H2O co-solvent system, and could be transformed into hollow microspheres constructed with α-Fe2O3 nanorods by calcining in air at 600 °C for 2 h. α-Fe2O3 hierarchical hollow microspheres with size about 320 nm in diameter were constructed by the radically oriented single-crystalline nanorods with length and diameter of about 20–40 nm and 15–20 nm, respectively. The investigation on the evolution formation revealed that SDBS was critical for controlling the assembly of the freshly formed nanocrystallites, and hollowing formation was proven to be the Ostwald ripening process by tracking the structure of the products at different growth stages. Scanning electron microscopy, X-ray diffraction, transmission electron microscopy, and high-resolution transmission electron microscopy were used to characterize the structure of the synthesized products. An investigation of the gas-sensing properties showed that α-Fe2O3 hierarchical hollow spheres exhibited high gas response to ethanol at the optimum working temperature of 300 °C.